High-altitude exposure reduces inspiratory muscle strength - Fasano, V.; Paolucci, E.; Pomidori, L.; Cogo, A. (International Journal of Sports Medicine, 2007)
It was the aim of the study to assess the maximal pressure generated by the inspiratory muscles (MIP) during exposure to different levels of altitude (i.e., hypobaric hypoxia). Eight lowlanders (2 females and 6 males), aged 27 - 46 years, participated in the study. After being evaluated at sea level, the subjects spent seven days at altitudes of more than 3000 metres. On the first day, they rode in a cable car from 1200 to 3200 metres and performed the first test after 45 - 60 minutes rest; they then walked for two hours to a mountain refuge at 3600 metres, where they spent three nights (days 2 - 3); on day 4, they walked for four hours over a glacier to reach Capanna Regina Margherita (4559 m), where they spent days 5 - 7. MIP, flow-volume curve and SpO2 % were measured at each altitude, and acute mountain sickness (Lake Louise score) was recorded. Increasing altitude led to a significant decrease in resting SpO2 % (from 98 % to 80 %) and MIP (from 134 to 111 cmH2O) (baseline to day 4: p < 0.05); there was an improvement in SpO2 % and a slight increase in MIP during the subsequent days at the same altitude. Expiratory (but not inspiratory) flows increased, and forced vital capacity and FEF75 decreased at higher altitudes. We conclude that exposure to high altitude hypoxia reduces the strength of the respiratory muscles, as demonstrated by the reduction in MIP and the lack of an increase in peak inspiratory flows. This reduction is more marked during the first days of exposure to the same altitude, and tends to recover during the acclimatisation process.